Design of identity authentication agreement in mobile terminal based on SM2 algorithm and blockchain - Qiuhan WU; Wei HU (网络与信息安全学报)
To solve the privacy leakage problem in the process of identification by second generation residents’ ID card,the SM2 algorithm and the blockchain technology were adopted,and the dynamic password ,facial recognition and two-dimension code to modify the traditional identification method were combined to design a kind of identification agreement on mobile terminal.The study analyzed the efficiently and security of the agreement,which reflected that the agreement could guarantee users’ privacy when it provide high-efficient identification.